-5(-4x-5)=-7+8(x+1)

Simple and best practice solution for -5(-4x-5)=-7+8(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(-4x-5)=-7+8(x+1) equation:


Simplifying
-5(-4x + -5) = -7 + 8(x + 1)

Reorder the terms:
-5(-5 + -4x) = -7 + 8(x + 1)
(-5 * -5 + -4x * -5) = -7 + 8(x + 1)
(25 + 20x) = -7 + 8(x + 1)

Reorder the terms:
25 + 20x = -7 + 8(1 + x)
25 + 20x = -7 + (1 * 8 + x * 8)
25 + 20x = -7 + (8 + 8x)

Combine like terms: -7 + 8 = 1
25 + 20x = 1 + 8x

Solving
25 + 20x = 1 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
25 + 20x + -8x = 1 + 8x + -8x

Combine like terms: 20x + -8x = 12x
25 + 12x = 1 + 8x + -8x

Combine like terms: 8x + -8x = 0
25 + 12x = 1 + 0
25 + 12x = 1

Add '-25' to each side of the equation.
25 + -25 + 12x = 1 + -25

Combine like terms: 25 + -25 = 0
0 + 12x = 1 + -25
12x = 1 + -25

Combine like terms: 1 + -25 = -24
12x = -24

Divide each side by '12'.
x = -2

Simplifying
x = -2

See similar equations:

| 6+4x-2y=0 | | 4y-13=-2-3y | | -74=-2(6x+4)+6(1-2x) | | 8y-21=12y-29 | | 3x^2-53x=-56 | | 6--3x=5x-10x+18 | | 3(3.41)+2(0.99)+4h=19.29 | | t+18.1=23.1x | | .037x+.079(.01-x)=.065(.01) | | 4(2x-8)=8(4x+2) | | 7(-5r-5)-8=4(1+5r)-8r | | 5y*3y=24 | | 5x+3=7x-27 | | 10x+3(5)=20 | | x/3-3=5/6 | | 5=5-7n-5n | | X-4+7=0 | | -7(-3+a)=-a+5(-4a+7) | | 3(2a-5)+1=4 | | -2(8n-1)-7(-n+5)=1-3n+2-3n | | 1.25x+x^2= | | y=-0.2x^2-32x+2 | | 4x+6x-2(x-2)=3(4x+7) | | x=10+.25X | | lnx+2(lnx^2)=6 | | lnx-2(lnx^2)=6 | | B-9+6b=40 | | 380=40t+60t-120 | | 2x+-5x+(8x+6x)=5 | | 2x-5x+(8x+6x)=x | | a=p+1fora | | -208=4x+7(-6x-8) |

Equations solver categories